Investigating active travel to primary school in Ireland. Issue 6 (20th August 2014) - Daniels, Natasha; Kelly, Colette; Molcho, Michal; Sixsmith, Jane; Byrne, Molly; Nic Gabhainn, Saoirse
Abstract : Purpose: Active travel to school, by walking or cycling, can positively influence children's health as a possible means of increasing physical activity. This study investigates the context of, promoters and barriers, and the required actions and actors that need to be involved to address each of these. Design/methodology/approach: It does so by utilizing a health promoting mixed-methods research methodology, participatory research coupled with quantitative research methods. This sample consisted of 73 children aged between 11 and 13 years from four primary schools in the West of Ireland. A self-completion questionnaire was followed by a participative approach to facilitate the children to share their opinions as freely as possible. Findings: Overall 30.1% of children reported that they actively travelled to school. A greater proportion of children from urban and disadvantaged schools actively travelled. Proximity to the school was the most frequently reported promoter and barrier. The participative research enabled the children to identify many actors that need to be involved in enacting the promoters and eliminating the barriers and the need for a multi-sectoral approach to improve rates of active travel to school in Ireland. Originality/value: Adopting a participative approach allowed for the use of a health promoting research process, thus empowering the children to participate in groups and develop the data themselves. The children confirmed that they have a relevant and valuable understanding of the process necessary to address active travel to school as a public health issue in Ireland.